Temporomandibular joint disorders, happiness, and COMT, HTR2A and FKBP5 polymorphisms in adolescents: a cross-sectional study - Ana Luiza Peres BALDIOTTI; Gabrielle AMARAL-FREITAS; Mariane Carolina Faria BARBOSA; Paula Rocha MOREIRA; Renata de Castro MARTINS; Renato Assis MACHADO; Ricardo Della COLETTA; Michelle Nascimento MEGER; Saul Martins PAIVA; Rafaela SCARIOT; Fernanda de Morais FERREIRA (Brazilian Oral Research)
Abstract Temporomandibular joint disorder (TMD) has a multifactorial etiology involving psychological and genetic aspects. This condition commonly begins in adolescence, which is a period of emotional, physical, and psychological maturation. The aim of the present study was to investigate associations between temporomandibular joint (TMJ) disorder and happiness as well as polymorphisms in the COMT, HTR2A, and FKBP5 genes in Brazilian adolescents. A cross-sectional study was conducted with 90 adolescents aged 13 to 18 years. TMD was diagnosed using the RDC/TMD. The Subjective Happiness Scale (SHS) was used to assess happiness. Saliva samples were collected for the analysis of genomic DNA and genotyping of single nucleotide polymorphisms in the COMT (rs165656, rs174675), HTR2A (rs6313, rs4941573), and FKBP5 (rs1360780, rs3800373) genes using real-time PCR (Taqman method). Bivariate, unadjusted, and adjusted binary logistic regression analyses were performed (p < 0.05). Happiness was associated with TMD in the adolescents (OR=1.37; 95%CI: 1.02–1.85; p = 0.037). The rs174675 polymorphism in the COMT gene was significantly associated with TMD (OR = 0.18; 95%CI: 0.04–0.74; p = 0.018). No associations were found between TMD and polymorphisms in HTR2A and FKBP5 genes (p > 0.05). TMD was associated with happiness, as adolescents who considered themselves less happy were more likely to have this disorder. The diagnosis of TMD was also associated with the rs174675 polymorphism in the COMT gene, as the prevalence of the disorder was higher among homozygous C Brazilian adolescents than in heterozygous CT individuals.